Investigation of the slip modulus between cold-formed steel and plywood sheathing - Martin, Geoff (Kansas State University, 2014)
Cold-formed steel members quickly are becoming a popular material for both commercial and residential construction around the world. Their high strength to weight ratio makes them a viable alternative to timber framing. In most cases cold-formed steel is used as a repetitive member in floor, wall, or roof assemblies. Structural sheathing is used in conjunction with the framing members in order to transfer loads between individual members. This sheathing is connected mechanically to the cold-formed steel through a variety of methods. The most common method uses screws spaced at close intervals, usually between 6 to 12 inches on center. When such assemblies are constructed, load is transferred from the sheathing through the connectors into the cold-formed steel, forming a composite assembly in which load is transferred and shared between two materials, providing a higher strength and stiffness over individual members themselves. The amount of load that can be transferred is dependent on the amount of slip that occurs when the assembly is loaded. This slip value describes the amount of composite action that takes place in the assembly. The amount of slip can be described by a value called the slip modulus. The composite, or effective, bending stiffness can be calculated using the slip modulus. In current design of cold-formed steel composite assemblies this composite action is not being taken into account due to a lack of research and understanding of the composite stiffness present in these assemblies. Taking composite action into account can lead to decreased member sizes or increased spacing of members, thereby economizing design. Furthermore, improved understanding of the effective stiffness can lead to more accurate design for vibrations in floor systems. This thesis tests cold-formed steel plywood composite members in an effort to verify previously established slip modulus values for varying steel thicknesses and establishes new values for varying fastener spacings. The slip modulus values obtained are used to calculate effective bending stiffness values in an effort to prove that composite action should be utilized in design of cold-formed steel composite assemblies.
Keywords: Cold-formed steel; Composite; Slip modulus; Architectural engineering (0462)